Study on airflow field and fiber motion with new melt blowing die. Issue 6 (1st April 2019) - Han, Wanli; Xie, Sheng; Shi, Jing; Wang, Xinhou
Abstract : In this study, a new melt‐blowing die was studied with the computational fluid dynamic approach. A bead‐viscoelastic element fiber model was established to model three‐dimensional paths of the fiber motion with the standard linear solid (SLS) constitutive equation in different airflow fields. The effects of this newly designed die on the velocity field, temperature field, and turbulence fluctuation field at the centerline were studied and compared with the traditional melt blowing die. The fiber motion was simulated and compared with the airflow field of different dies. The simulations results demonstrated that the new die was able to reduce the velocity fluctuations of the air flow near the outlet of the polymer capillary and generate the higher centerline air velocity and temperature. The fiber attenuation and motion were related to the centerline air velocity, temperature, and turbulent fluctuation in the melt blowing process. POLYM. ENG. SCI., 59:1182–1189 2019. © 2019 Society of Plastics Engineers